2021
DOI: 10.3390/plants10030592
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Germination on the Microstructural and Physicochemical Properties of Different Legume Types

Abstract: The microstructural and physicochemical compositions of bean (Phaseolus vulgaris), lentil (Lens culinaris Merr.), soybean (Glycine max L.), chickpea (Cicer aretinium L.) and lupine (Lupinus albus) were investigated over 2 and 4 days of germination. Different changes were noticed during microscopic observations (Stereo Microscope, SEM) of the legume seeds subjected to germination, mostly related to the breakages of the seed structure. The germination caused the increase in protein content for bean, lentil, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 87 publications
17
35
0
Order By: Relevance
“…The impact of temperature did not show a clear trend, since both low and high temperatures caused the highest carbohydrate increment, while medium temperatures were related with the lowest carbohydrate levels. In contrast, longer times reduced the content of carbohydrates in sprouted lentil flour, especially at higher temperatures ( Figure 1 c), findings in agreement with those reported in lentil germinated for 1–4 days [ 41 , 42 ]. The activation of a wide range of hydrolytic enzymes, including α-amylase, glucosidase, and dextranase existing in the aleurone layers, and β-amylase present in the endosperm that hydrolyze starch to produce energy [ 43 ] may be involved in the reduction of carbohydrate content during the germination.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The impact of temperature did not show a clear trend, since both low and high temperatures caused the highest carbohydrate increment, while medium temperatures were related with the lowest carbohydrate levels. In contrast, longer times reduced the content of carbohydrates in sprouted lentil flour, especially at higher temperatures ( Figure 1 c), findings in agreement with those reported in lentil germinated for 1–4 days [ 41 , 42 ]. The activation of a wide range of hydrolytic enzymes, including α-amylase, glucosidase, and dextranase existing in the aleurone layers, and β-amylase present in the endosperm that hydrolyze starch to produce energy [ 43 ] may be involved in the reduction of carbohydrate content during the germination.…”
Section: Resultssupporting
confidence: 89%
“…Germination temperature and time showed a linear impact on fat levels of sprouted lentil flour, but the mathematical model obtained showed a poor agreement between experimental and predicted data, considering the low R 2 value (0.34, data not shown). As depicted in Figure 1 b, germination caused a decrease in fat content during germination, with the lowest fat values at higher temperatures and longer times, in agreement with other authors, who observed reductions of lipid content from 17 to 68% in lentil germinated for 4–6 days at 25 °C [ 38 , 41 ]. The activation during sprouting of endogenous lipolytic enzymes that hydrolyze triacylglycerol to release free fatty acids, which are oxidized to produce energy for seedling development [ 38 ], is mainly responsible for the reduction in fat content in germinated lentil flour.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Different studies reported that beans contain a higher amount of protein than white wheat flour [ 23 , 90 ]. Taking into account that germination leads to an increase in the amount of protein in beans [ 91 ], then it may be concluded that the samples of bread with the GBF addition will contain a higher amount of proteins. The darkening of the bread samples with the increase amount of GBF addition could also be explained by the fact that the amount of phenolic compound increases [ 92 ].…”
Section: Discussionmentioning
confidence: 99%